Metodologia de avaliação dos impactos dos transportes urbanos em áreas de preservação histórica - Kanno, Simone Izumi Kubo (2008)
Historical preservation, nowadays, is a great challenge searching for the cultural identity in the cities. Property deterioration and degradation can be caused by a lot of factors, including the fast growth and development of the cities increase the traffic flow and in most of the cases request a widening of the road and, because of which buildings had to be demolished. Besides, a great traffic increases the number of pollutant in the atmosphere and vibration on buildings. This research intent to create a methodology to identifying, measuring, and quantifying how the degradation in historical buildings occurs. The area of the study will be in Uberlândia MG, a Brazilian median sized city. The method applied into this work consists in evaluating of two parameters: environmental pollution produced by transportation and the vibration that propagates in the ground by the movement of vehicles. The air pollution is quantified by Traffic Software Integrated System (TSIS) software which process a traffic flow and road characteristics based dynamic animation. Vibration was measured in Casa da Cultura, an important historic building of the city, with appropriate equipments.